Pengembangan Modul Ajar Metode Penerjemahan Melalui Pendekatan Kontekstual bagi Mahasiswa STAI Ali bin Abi Thalib Surabaya: Development of a Teaching Module on the Translation Method Using a Contextual Approach for Students of STAI Ali Bin Abi Thalib Surabaya - Zaki Ulien Nuha; Maryono; Mubarak Bamualim; Agustian Rahmadi (Educan, 2025)
This research aims to develop a teaching material book for the Translation Methodology course for Arabic Language Education students at STAI Ali bin Abi Thalib Surabaya. This teaching material is expected to strengthen students' learning motivation and provide clear guidance in the learning process. The development of this teaching material uses a Research and Development (R&D) model with the ADDIE approach, consisting of five stages: analysis, design, development, implementation, and evaluation. In the analysis stage, the researcher identifies the needs of the institution, students, and the learning syllabus. The design of the teaching material is tailored to the essential components of a good teaching book. In the development stage, the teaching material is created and validated by experts, teachers, and students. Implementation is carried out in both small and large groups to assess its effectiveness. Evaluation is conducted to assess how well the teaching material achieves its learning objectives. The results show that the final product, a Translation Methodology teaching material book with a contextual approach, can be used in the learning process for sixth-semester students. However, the evaluation indicates that improvements are still needed in terms of content, layout, and reading sources to enhance the teaching material. Further research is required to refine and improve the teaching material to make it more effective in supporting the teaching and learning process at STAI Ali bin Abi Thalib Surabaya.